(untitled) (Materiali di Estetica. Terza serie, 2016)
This short essay is a personal memory of Guido Neri, reconstructed from small details of everyday life placed in the office of the University of Verona: it goes from the favourite objects by the different schools of thought to the transformation of an umbrella stand into a saucer of a plant.